Does the Market Understand Rating Shopping? Predicting MBS Losses with Initial Yields - He, Jie (Jack); Qian, Jun (Q. J.); Strahan, Philip E. (Review of Financial Studies, 2016)
We study rating shopping on the MBS market. Outside of AAA, losses are higher on single-rated tranches than on multi-rated ones, and yields predict future losses for single-rated tranches, but not for multi-rated ones. Conversely, ratings have less explanatory power for single-rated tranches. These results suggest that single-rated tranches have been “shopped,” whereby pessimistic ratings never reach the market. For AAA-rated MBS, by contrast, 93% receive two or three such ratings, and those ratings agree 97% of the time. This ratings convergence suggests that agencies “cater” to investors, who cannot purchase a tranche unless it has multiple AAA ratings. Received January 22, 2014; accepted October 21, 2015 by Editor Andrew Karolyi.